The development and verification of clinical medication pathway for tic disorder in west China - Li, Dan; Yang, Chunsong; Zhang, Jianhua (Frontiers in Pharmacology, 2025)
BackgroundThe purpose of this study was to construct a clinical medication pathway for children with tic disorder (TD) and provide a reference for rational drug use for children with TD.MethodsA literature review was performed to develop an initial clinical medication pathway. Next, a two-round Delphi survey was implemented. A prospective cohort study was carried out to evaluate effectiveness of the constructed clinical medication pathway.ResultsIn total, 26 experts (80.8% doctors, 11.5% pharmacists, 7.7% nurses) from Level III medical institutions from west China were included in the Delphi survey. After two rounds of expert consultation, a clinical medication pathway was constructed, comprising 41 items across eight dimensions, these dimensions include participants of the clinical medication management, TD assessment, comorbidity assessment, treatment goals and plans, medication treatment for tics, medication treatment for comorbid attention deficit hyperactivity disorder, recurrence and referral management and medication adherence management. A total of 100 TD patients were consecutively recruited from the outpatient clinic, with 50 cases (8.01 ± 2.49, 35 male) assigned to the clinical medication pathway group and 50 cases (8.25 ± 2.49, 35 male) to the routine treatment group. After 12 weeks of treatment, the clinical medication pathway group showed higher scores in efficacy rate (82% vs. 58%, p = 0.009), YGTSS score (23.86 ± 6.53 vs. 30.68 ± 7.26, p < 0.000), medication adherence (7.47 ± 0.746 vs. 4.32 ± 1.391, p < 0.000) and in the caregivers’ ratings of service quality (4.46 ± 0.706 vs. 4.10 ± 0.839, p = 0.022), service attitude (4.28 ± 0.701 vs. 3.80 ± 0.881, p = 0.003), service efficiency (4.20 ± 0.990 vs. 3.78 ± 1.016, p = 0.039), professional level (4.36 ± 0.631 vs. 3.94 ± 0.956, p = 0.011), and visit satisfaction (4.44 ± 0.675 vs. 3.94 ± 0.956, p = 0.011) compared to the routine treatment group.ConclusionThis study actively explored clinical medication pathways for children with TD in China and provided a standardized and highly operable medication pathway for reference in clinical practice. This pathway is expected to be widely used in treatment for children with TD. We suggest that further research should update and improve the clinical medication pathway using the latest evidence.